Kajian Standarisasi Ruang pada Pusat Kegiatan Mahasiswa dengan Studi Kasus Bangunan Student Center Kampus di Indonesia - Wahyu Tirta Nugraha; Samsul Bahri (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
A university considered excellent in this century is a global university. Universities across Indonesia have also taken the initiative to move in this direction by improving various facilities and infrastructure. The desire to implement, develop, and enhance education, research culture, and community service programs aims to improve academic quality by advancing superior knowledge that benefits societal transformation for a better life. Additionally, universities strive to continuously improve the quality of learning management to achieve excellence in national and international competition and collaboration. This vision, mission, and goal are generally shared by campuses throughout Indonesia. The aspiration is to create students capable of applying knowledge, technology, arts, and humanities while producing outstanding human resources who excel not only academically and professionally. According to Law No. 12 of 2012, Article 14, Paragraph (1), students need to develop their talents, interests, and abilities through co-curricular and extracurricular activities as part of the educational process. Therefore, facilities that support students' development and innovation within the campus environment are needed. One example is the construction of a Student Activity Center.